2015
DOI: 10.5539/jas.v7n10p271
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Some Garlic Varieties under Drought Stress Conditions

Abstract: Currently in Egypt the tendency is to counteract some negative effects caused by the climatic, edaphic changes and political conflicts on the Nile River water. So, the field experiment was carried out to provide a review of differential responses for four cultivars and adaptations under three levels of drought stress during two growing seasons (2012/2013 and 2013/2014). According to drought resistance indices i.e., drought tolerance index, yield injury %, superiority measure and relative performance, Egaseed 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…As observed in Table 3, drought induced carotenoid accumulation when compared to the control, except in FS samples. In general, the estimated values of pigments in this study agree with those cited in the literature, in which the concentration of chlorophyll and carotenoid increases in the tolerant species exposed to water deficiency (Hancı and Cebecı, 2014;Badran, 2015;Husseind and El-Faham, 2018). Similarly, Kıran (2019) found that chlorophyll and carotenoid level in lettuce leaves grown in vermiculite under drought stress were higher when compared to the control plants.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As observed in Table 3, drought induced carotenoid accumulation when compared to the control, except in FS samples. In general, the estimated values of pigments in this study agree with those cited in the literature, in which the concentration of chlorophyll and carotenoid increases in the tolerant species exposed to water deficiency (Hancı and Cebecı, 2014;Badran, 2015;Husseind and El-Faham, 2018). Similarly, Kıran (2019) found that chlorophyll and carotenoid level in lettuce leaves grown in vermiculite under drought stress were higher when compared to the control plants.…”
Section: Resultssupporting
confidence: 91%
“…The maximum number of cloves were noted in FS-CHICKEN-IPT and FS-CATTLE-GOAT samples (9.27, 9.12), whereas the lowest number was recorded in FS-NPT, FS-IPT, and FS samples as 3.77, 3.84, and 3.86, respectively (Table 5). Based on the yield data, the drought resistance of FS-CATTLE-GOAT, FS-CHICKEN-GOAT, FS-CATTLE, and FS-GOAT-NPT samples were found to be higher than control, but FS, FS-IPT, and FS-NPT samples were observed to be susceptible (Alphonse et al, 2015;Badran, 2015). The presence of goat and chicken manures in the groups with the highest measured values in garlic bulbs indicated that these soil mixtures make a significant contribution toward overcoming drought stress (Daba et al, 2018;Doğan et al, 2020).…”
Section: Bulbs Yield Cloves and Chemicalsmentioning
confidence: 99%
“…Salinity tolerant variety can satisfy is determined as genotype which achieves considerably greater productivity than average under salinity stress. The data in Table 3 can distribute the studied quinoa cultivars based on grain yield under both non-stress and salinity stress and these results are harmonic with Majidi et al (2011), and Badran and Moustafa (2014) and Badran (2015) who stated that STI, HM (harmonic mean) and MP (geometric mean productivity) can be effective indices for pick out high productivity varieties under both non-stress and salinity stress [3,33,34]. According to the results in Table 4 can be useful to divide the tested cultivars into three groups based on their grain yield as follow: the first group, good express cultivar behavior in both normal and salinity stress (i.e.…”
Section: Tolerance Parameterssupporting
confidence: 71%
“…Leaf area (cm 2 ) = (Fresh weight of leaves/ Fresh weight of disks) × Area of the disk 4) Amount of chlorophyll (SPAD units) was measured using chlorophyll Meter SPAD-502 (33) . 5) Determination of nitrogen, phosphorus and potassium: N was estimated using the Kjeldahl method (34) .…”
Section: Measurements Of Plant Growthmentioning
confidence: 99%